2008
DOI: 10.4026/1303-2860.2008.0087.x
|View full text |Cite
|
Sign up to set email alerts
|

Work Related Factors That Affect Burnout Among Accounting And Finance Academicians

Abstract: ÖZET Bu çalışmanın amacı, Türkiye'deki akademisyenlerin tükenmişlik düzeylerini ölçmek ve akademisyenlerin tükenmişlik düzeylerini etkileyen faktörleri araştırmaktır. Veriler, toplam 78 kamu üniversitesinin ve özel üniversitenin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…According to the results, factors related to educational background proved to have no effect on teachers' burnout levels. The only significant result revealed that is related to work related factors is the relation between the Emotional Exhaustion level and perceived stress level, which is congruent with previous studies (Suzumura, Tachi, Takeynama, Ebara, Sakai, and Itani, 2007;Eker and Anbar, 2008).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…According to the results, factors related to educational background proved to have no effect on teachers' burnout levels. The only significant result revealed that is related to work related factors is the relation between the Emotional Exhaustion level and perceived stress level, which is congruent with previous studies (Suzumura, Tachi, Takeynama, Ebara, Sakai, and Itani, 2007;Eker and Anbar, 2008).…”
Section: Resultssupporting
confidence: 89%
“…After scoring burnout inventory, correlations between burnout levels and personal factors, educational background and work related factors (Eker and Anbar, 2008) as well as instructors' perceived stress level were calculated to answer the research questions.…”
Section: Methodsmentioning
confidence: 99%
“…Expectations to publish in top journals are rising and are exacerbated by the comparatively small number of top‐ranked accounting journals . These and other factors are claimed by Eker and Anbar () to place academics in an occupational category susceptible to burnout.…”
Section: Introductionmentioning
confidence: 89%
“…The results of this study suggest the presence of key elements of burnout among Australian and New Zealand accounting academics, with participants commenting on high levels of cynicism, stress and exhaustion. Consistent with prior literature, the findings of this study indicate increasing job dissatisfaction in the accounting academy (Dua, ; Bellamy et al ., ; Duff and Monk, ; Pop‐Vasileva et al ., ) as well as evidence of burnout (Eker and Anbar, ; Byrne et al ., ). However, professional efficacy remains high, which is a mitigating factor against burnout.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…Hence, the consequences of burnout are pervasive. Burn out diminishes mental and physical vigor of experiencing subjects (Eker & Anber, 2008), causes mental and physical fatigue, sleeplessness, and family issues and may also lead to extensive consumption of drugs and liquors (Maslach & Jackson, 1981). Burn out diminishes productivity and efficiency of individuals which in turn affect the levels of their satisfaction with jobs, and commitment with organizations (Chong & Monroe, 2015).…”
Section: Burnout Turnover Intentions and Workplace Incivilitymentioning
confidence: 99%